Maternal education and sibling inequalities in child nutritional status in Ethiopia. (March 2022) - Bras, Hilde; Mandemakers, Jornt
Abstract: In many societies child nutritional status varies between siblings because of parental gender and birth order preferences and differential intra-household resource allocation. While more educated women have been found to improve children's nutrition overall, it is unclear whether they also buffer sibling inequalities in nutritional status. We study the interplay between parental preferences, maternal education, and sibling inequalities in child nutritional status in Ethiopia, the second most populous country in sub-Saharan Africa, with high rates of malnutrition, rapid socio-economic change, urban fertility decline, and low, but increasing female education. We base our analysis on a pooled sample of the 2011/12, 2013/14, and 2015/16 waves of the Ethiopian Socioeconomic Survey using 8275 observations from 4402 children between the age of six months and 9 years old nested in 1687 households. Results from multilevel and fixed effects models show sizable gender and birth order differences in nutritional status. Boys had a better nutritional status than girls and earlier born children had a better nutritional status than later born children, both in terms of height-for-age and weight-for-age. More educated mothers buffered sibling inequalities in nutritional status according to birth order, but not according to gender. The height penalty of being a higher order child disappeared for children whose mothers had about eight years of education or more (primary school finished/some secondary school). The beneficial impact of maternal education, counteracting some within-family inequalities, asks for continued investments in girls' and women's education. Highlights: The maternal education and siblings' nutrition relationship is not well understood. We found steep gender and birth order gradients in child nutritional status. Educated mothers buffer sibling inequalities in nutrition according to birth order. Educated mothers do not compensate inequalities between boys and girls. Maternal education's influence is independent of household wealth and residence.